Jogos no Ensino da Matemática. - Mota, Paula Cristina Costa Leite de Moura (2013)
O trabalho apresentado foi elaborado a partir de estudos teórico-práticos relacionados com a utilização do jogo no processo ensino-aprendizagem da Matemática. Inicialmente procuramos definir o termo jogo e os diversos tipos de jogos existentes, referimos a utilização dos jogos no ensino em geral e, posteriormente, salientamos também a importância deste recurso metodológico nas aulas de Matemática. Em seguida, explicitamos os momentos do jogo, o desenvolvimento dos conceitos matemáticos através desta actividade e também sua importância para o desenvolvimento da habilidade de cálculo mental. Terminámos esta parte com a apresentação de alguns jogos, e das suas respectivas potencialidades didáctico-pedagógicas, que podem ser usados dentro e fora da sala de aula. Na última parte do trabalho, realizamos uma pesquisa com alguns professores do ensino básico com o intuito de verificar se eles usam o jogo para ensinar ou consolidar conceitos matemáticos e de que forma o fazem. Analisando esta pesquisa verificamos que a percentagem de docentes que utilizam jogos ainda é reduzida. Entre os que fazem uso deste recurso, alguns não exploram devidamente as potencialidades pedagógicas do jogo, esquecendo que são estas que contribuem muito para a aprendizagem dos conceitos matemáticos. The work here presented has been developed from theoretical and practical studies on the use of games in the mathematics teaching and learning process. After establishing the definition of the word “game” and introducing different types of games available, their use in education in general is mentioned and the importance of this methodological tool in Maths lessons is stressed. Next we elucidate the stages in the game, the development of mathematical concepts through this kind of activity and also its importance to the development of mental calculation skills. Finally some games are presented, which can be used inside and outside the classroom, and their educational and pedagogical potential is assessed. In a second part of this project, a search was conducted, with some primary school teachers, in order to check if games are used to teach or consolidate mathematical concepts, at this level, and how it is done. Some conclusions can be drawn from data analysis: first, the percentage of teachers who use games is still small; second, some of the teachers who use games do not fully explore their pedagogical potential yet, forgetting this potential is the most important in the learning process of mathematical concepts.The work here presented has been developed from theoretical and practical studies on the use of games in the mathematics teaching and learning process. After establishing the definition of the word “game” and introducing different types of games available, their use in education in general is mentioned and the importance of this methodological tool in Maths lessons is stressed. Next we elucidate the stages in the game, the development of mathematical concepts through this kind of activity and also its importance to the development of mental calculation skills. Finally some games are presented, which can be used inside and outside the classroom, and their educational and pedagogical potential is assessed. In a second part of this project, a search was conducted, with some primary school teachers, in order to check if games are used to teach or consolidate mathematical concepts, at this level, and how it is done. Some conclusions can be drawn from data analysis: first, the percentage of teachers who use games is still small; second, some of the teachers who use games do not fully explore their pedagogical potential yet, forgetting this potential is the most important in the learning process of mathematical concepts.